Three-Dimensional Imaging and Quantitative Analysis of Blood Vessel Distribution in The Meniscus of Transgenic Mouse after Tissue Clearing - Huaixuan Sheng; Mingru Huang; Huizhu Li; Luyi Sun; Sijia Feng; Xiner Du; Yicong Wang; Xiaoyu Tong; Yi Feng; Jun Chen; Yunxia Li (Cell Journal, 2023)
Objective: Blood supply to the meniscus determines its recovery and is a reference for treatment planning. This studyaimed to apply tissue clearing and three-dimensional (3D) imaging in exploring the quantitative distribution of bloodvessels in the mouse meniscus.Materials and Methods: In this experimental study, tissue clearing was performed to treat the bilateral knee joints oftransgenic mice with fluorescent vascular endothelial cells. Images were acquired using a light sheet microscope andthe vascular endothelial cells in the meniscus was analysed using 3D imaging. Quantitative methods were employedto further analyse the blood vessel distribution in the mouse meniscus.Results: The traditional three-equal-width division of the meniscus is as follows: the outer one-third is the red-red zone(RR), the inner one-third is the white-white zone (WW), and the transition area is the red-white zone (RW). The divisionrevealed significant signal differences between the RW and WW (P<0.05) zones, but no significant differences betweenthe RR and RW zones, which indicated that the division might not accurately reflect the blood supply of the meniscus.According to the modified division (4:2:1) in which significant differences were ensured between the adjacent zones,we observed that the width ratio of each zone was 38 ± 1% (RR), 24 ± 1% (RW), and 38 ± 2% (WW). Furthermore, theblood supply to each region was verified. The anterior region had the most abundant blood supply. The fluorescencecount in the anterior region was significantly higher than in the central and posterior regions (P<0.05). The blood supplyof the medial meniscus was superior to the lateral meniscus (P<0.05).Conclusion: Analysis of the blood supply to the mouse meniscus under tissue clearing and 3D imaging reflectquantitative blood vessel distribution, which would facilitate future evaluations of the human meniscus and providemore anatomical references for clinicians.